Tindak Tutur Deklarasi Pedagang Kakilima dalam Bahasa Mandailing di Pusat Pasar Ujung Gading Kecamatan Lembah Melintang Kabupaten Pasaman Barat - Syafruddin, Syafruddin; Amir, Amril; Tressyalina, Tressyalina (Universitas Negeri Padang, 2012)
This is purpose thorough. 1) describe type speech action declaration merchant five foot in the Mandailing language. 2) fuction type speech action declaration merchant five foot in the Mandailing language. 3) strategy type speech action declaration merchant five foot in the Mandailing language. This is data through speech merchant five foot in the Mandailing language in the otter merchant dise stock to candidate buyer in the Ujung Gading market. This assamble technigue data conduct with see rakam technigue instrument on the thorough this is through self assist with tool shaped recorder tape. Finding this is through.1) there is four shapeds speech action declaration the use merchant five foot in the serve buyer that’s. (a) speech action decide, (b) speech action cancel, (c) speech action forbicl, and (d) speech action permission. 2) receive four function speech action declation the use merchant five foot on the serve buyer is. (a) competitive, (b) convivial, (c) collaborative, and (d) conflictive. There is four strategy action the use merchant five foot on the serve buyer is. (a) strategy action not offer, (b) srategy action help positive, (c) strategy action help negative, and (d) strategy action indistinct.